LITERATURE REVIEW : PENERAPAN COUNTER PRESSURE UNTUK MENGURANGI NYERI PERSALINAN KALA I - Erni Juniartati; Melyana Nurul Widyawati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
The Pain is a natural process of labor, but if not handled properly, it will cause another problem, namely increasing anxiety in the labour process. So that the production of adrenaline hormone increases and results in vasoconstriction that causes maternal blood flow to the fetus to fall. During this time, pain management using drugs but many drugs except expensive, contains a side effect too. So, non pharmacological methods are more recommended because they safe for pregnant women. One of the non pharmacological recommended is Counter Pressure. Article searching conducted in some databases: Google Scholar, Proquest and Science Direct. Keyword used were “Counter Pressure”, “pain”, Labour”and finally got 10 articles matched (4 international articles and 6 national articles). Counter Pressure could be categorized as a safe and effective intervention to reduce labor pain at first phase. Using Counter Pressure will close the pain stimulus that will be delivered to the spinal cord and brain. Endorphin compounds will be activated at Counter Pressure so that the transmission of pain messages can be inhibited which can cause significant decrease in pain sensation. Counter Pressure could reduce labour pain at first phase.